Polaronic distortion and vacancy-induced magnetism in MgO - Sanvito, Stefano; Droghetti, Andrea (My University, 2010)
The electronic structure of the neutral and singly charged Mg vacancy in MgO is investigated using density functional theory. For both defects, semilocal exchange correlation functionals such as the local spin density approximation incorrectly predict a delocalized degenerate ground state. In contrast, functionals that take strong correlation effects into account predict a localized solution, in agreement with spin resonance experi- ments. Our results, obtained with the HSE hybrid, atomic self-interaction corrected and LSDA + U functionals, provide a number of constraints to the possibility of ferromagnetism in hole doped MgO.
PUBLISHED
Keywords: density-functional theory; Nanoscience & Materials